Transformation of Slovakian Youth Religiosity - Ondrej Štefaňak (Central European Journal of Educational Research, 2020)
Some sociologists of religion think that countries in Central and Eastern Europe are expected quick and rapid secularization. Therefore it is interesting to continuously search out, how the religiosity of Slovakian youth is transformed against the background of continual social and culture changes. The main goal of the presented paper, based especially on its own empirical researches of 2006 and 2016, is a description related to the transformation of youth’s religiosity in Slovakia (an example of Spiš Diocese). The presented work is situated in the area of religion sociology and shows also the typology transformation of the sought out youth’s religiosity that is very useful. Empirical analyses are based on, linked to or compared with main models of changes in religiosity in the contemporary world.